The Effect of Promotion, Ease of Transaction, and Trust on Purchase Decision of Shopee Pay Later Users - Veronica Agustin Nagayo (Jurnal Performa)
This research is done with the purpose of analyzing the effect of promotion, ease of transaction, and trust on purchase decision of Shopee Pay Later users as payment method. The cause of doing research towards Shopee Pay Later is there is the increase of Shopee Pay Later users that are influenced by incessant promotion, obstacle when using the account that is related to ease of transaction, and users’ complaint due to account hacking that is related to consumer trust. Sampling technique is with purposive sampling method. The questionnaires are distributed online by using Google Form with the number of respondents that are collected as many as 132 people and the respondents who passed the research criteria are 111 people. Data is analyzed by using multiple linear regression analysis.